2020
DOI: 10.3389/fonc.2020.01113
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Serum Exosomes From Patients With Metastatic Gastric Cancer

Abstract: Background: Clinical management of metastatic gastric cancer (mGC) remains a major challenge due to a lack of specific biomarkers and effective therapeutic targets. Recently, accumulating evidence has suggested that exosomes play an essential role in cancer metastasis and can be an excellent reservoir of novel biomarkers and candidate therapeutic targets for cancer. Therefore, in this study, we aimed to reveal the proteomic profile of mGC-derived exosomes. Methods: Exosomes were isolated from pooled serum samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 60 publications
7
47
0
1
Order By: Relevance
“…Proteasome 20S subunit alpha (PSMA) 3, PSMA4 , PSMA5 , tripartite motif containing 9 (TRIM9), and GTP cyclohydrolase 1(GCH1) were the top 5 hub genes. PSMA is a proteasome subunit alpha type associated with the occurrence and development of multiple cancers [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proteasome 20S subunit alpha (PSMA) 3, PSMA4 , PSMA5 , tripartite motif containing 9 (TRIM9), and GTP cyclohydrolase 1(GCH1) were the top 5 hub genes. PSMA is a proteasome subunit alpha type associated with the occurrence and development of multiple cancers [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Liquid biopsies may also help diagnose resistance to treatment before radiological progression and are gaining more relevance as a tool for optimizing patient care. The serum exosome proteome of metastatic gastric cancer patients was defined recently in detail by Ding et al [ 75 ]. A study showed that, in gastric cell lines, exosomal Ribosomal Protein S3 (RPS3) secreted by cisplatin-resistant tumor cells could be taken up by cisplatin-sensitive cells and thus become chemoresistant (through activation of the PI3K-Akt-cofilin-1 signaling pathway) [ 76 ].…”
Section: The Role Of Liquid Biopsy In Disease Monitoringmentioning
confidence: 99%
“…The AUC of this meaningful study was 0.923, and this approach is expected to become a highly accurate method for detecting early GC. For patients with metastatic GC, Ding et al [ 169 ] provided a comprehensive description of the serum sEVs-proteome and found that several subunits might act as biomarkers and therapeutic targets.…”
Section: Application Prospects Of Sevs In Gcmentioning
confidence: 99%